Prevalence Of Basal Stem Rot Disease Caused by Ganoderma Sp. On Oil Palm (Elaeis Guineensis Jacq) In Ghana (Journal of Science and Technology, 2024)
Oil palm (Elaeis guineensis Jacq.) is the most productive and highest yielding edible oil crop in the world, being 13 times more productive than soybean and other oil-bearing seeds. In 020/2021, a survey was conducted to assess incidence and severity of Ganoderma Basal Stem Rot (BSR) disease on selected palm trees in Central, Eastern, and Western regions of Ghana. A follow-up survey was conducted in 2022 to determine the current prevalence of the infection. A Ganoderma disease census was done based on the single-point assessment following the Standard Operating Procedure (SOP), with disease severity scale of 0-4 based on number of Basidiocarps per infected plant. A total of 7,500 palm trees from fifteen plantations were assessed. The number of fruiting bodies/basidiocarps per plant ranged from 2 to 291. Out of 15 plantations, 73% showed Ganoderma infection. Current study showed eight infected palms identified in Western region against two palms in 2020/2021. In Central region, one of the heavily infected palms identified on plot (B37-1) in 2021, was completely destroyed by the pathogen. Eastern region showed maximum presence of inoculum loads of Ganoderma pathogen with total number of 52 infected palms. Although, the disease incidence per selected plantations was low, (